CAD/CAM dentistry – review of materials based on literature - Bartkowiak, Tomasz; Idzior - Haufa, Małgorzata; Hędzelek, Wiesław (Journal of Stomatology, 2015)
CAD/CAM systems allow dental practitioners to provide their patients with chairside-produced restorations. Materials for these restorations comprise blocks made of feldspathic, leucite- and lithium disilicate-reinforced ceramics and nanoceramics. These materials are suitable for fabricating veneers, inlays, onlays and crowns. CAD/CAM blocks are structurally reliable, homogenous materials with little internal voids resulting in better mechanical properties than their laboratory counterparts. CAD/ CAM restorations from feldspathic ceramics are aesthetic, but have inferior mechanical properties than reinforced ceramics. The main failure causes are ceramic and tooth fracture. Reinforced ceramics offer higher flexural and fracture strength confirmed by in vitro studies but not many long-term clinical studies are available. Literature on nanoceramics includes in- vitro studies and case reports. Chairside CAD/CAM restorations are a reliable option for single-tooth restorations, but the use of newer materials requires further clinical investigation. The choice of the best material to match the clinical situation is a dentist’s task and many factors must be taken into account.